The role, impact, and responsibilities of health experts on social media. A focus group study with future healthcare workers - Engebretsen, Martin (Frontiers in Communication, 2024)
People are increasingly turning to social media platforms to acquire information and seek advice on health matters. Consequently, a growing number of qualified healthcare professionals are using social media as channels for public health communication. On platforms such as YouTube and Instagram, health workers can reach a wide and interested audience while applying powerful tools for presentation and interaction. However, such platforms also represent certain challenges and dilemmas when doctors and psychologists become health influencers. Who do they represent? What style of communication is expected? And what responsibilities do they have towards their followers? The present study contributes to the field of investigation by employing qualitative methods. It is based on three focus group interviews conducted with students enrolled in health-related study programmes at Norwegian universities. The paper asks: How do future healthcare workers perceive the social media practices of popular healthcare experts regarding the advantages and dilemmas associated with such practices?